Democratic Socialists on Social Media: Cohesion, Fragmentation, and Normative Strategies - Christopher C Barnes (tripleC: Communication, Capitalism & Critique)
This essay focuses on members of the Democratic Socialists of America (DSA) political organisation in the US and the ambivalence of using social media as a primary means of communication for socialist information and culture. Relying on in-depth interviews with fifteen active members and leaders in DSA, this essay asks: How does socialist communication on social media encourage both cohesion and fragmentation for activists within the DSA? Locating and analysing key tensions felt by DSA members in response to their use of Facebook and Twitter, this project sheds light on the ways in which socialism is presently communicated to publics and counterpublics and identifies important challenges for the expansion of the socialist movement.